The Equilibrium Relationships between Performance-Based Pay, Performance, and the Commission and Detection of Fraudulent Misreporting - Qiu, Buhui; Slezak, Steve L. (The Accounting Review, 2019)
ABSTRACT We develop an agency model in which managerial information manipulation creates pooling and entails ex post costs internal and/or external to the firm. We examine the implications of the strategic interactions between shareholders (who set internal governance and managerial incentive compensation), the manager (who exerts effort and reports on its outcome), and an external regulatory authority or RA (who investigates for fraud and levies penalties ex post). When the RA cannot pre-commit to an ex post investigation strategy, a fraudulent equilibrium obtains if the firm's internal governance costs are sufficiently high. Consistent with (so far fairly scant) post-SOX empirical evidence, but the opposite of the implications of signal-jamming models and equilibria with pre-commitment, the model implies an increase in minimum internal governance standards or ex post fraud penalties (as with SOX) results in decreased equilibrium pay-for-performance sensitivity and firm performance.